Synthesis and biological activities of aminoquinones, quinolines and their ruthenium(II) complexes - Amalyn Nain Perez (2018)
Aminoquinones are an important class of naturally-occurring and synthetic compounds with a wide variety of biological functions. Although several studies address pharmacological activity, only a few studies about these compounds exhibiting agrochemical activity have been reported to date. In this context, this project will address the synthesis of a class of aminoquinones called abenquines. Moreover, an investigation about both agrochemical and cytotoxic activities of this class of compounds is reported. Additionally, this work presents an exploration of the synthesis and biological activities of ruthenium complexes. Metals have been used for medicinal purposes for decades; among them, ruthenium compounds. There is increasing interest in the use of the latter because of their biological activities. Consequently, organic compounds such as aminoquinones or quinolines, with known biological activities, are used as N,Otype ligands to form stable complexes with ruthenium. In this regard, the synthesis of ruthenium complexes containing this class of ligands, as well as the evaluation of cytotoxic or antimicrobial property is described. Thereby, this thesis is divided into five chapters. In Chapter one, the first total synthesis of Abenquines A, B2, C, and D, is described. Abenquines have been achieved in three steps, with overall yields of 41-61%. The key steps of synthesis include (i) acylation of the aniline, (ii) oxidative demethoxylation, and (iii) oxidative addition of the amino acid moiety. Using the same methodology described above, in chapter two the synthesis of new analogues of abenquines is then discussed. Replacing the acetyl by a benzoyl group in the quinone core and changing the amino acid moiety with different amine groups results in 11 analogues with yields between 45-85%. The two most effective analogues carrying ethylpyrrolidinyl and ethylpyrimidinyl with either an acetyl group (2.1, 2.2) or a benzoyl group (2.11, 2.12), inhibited the proliferation of all five cyanobacterial strains tested, with IC50 values ranging from 0.3 to 3 µM. Furthermore, analogues 2.1, 2.2, 2.11, and 2.12, were the most potent against all human cancer cell lines and displayed EC50 between a range of 0.63.4 µM. Other series of analogues of abenquines were prepared by changing the amino acid group on abenquine with benzylamines and the acetyl with different acyl groups. This resulted in 14 new analogues in 68-95% yield as described in Chapter 3. Some analogues 3.2,3.3, 3.6, and 3.7 presented high effectiveness (IC50 = 0.1-0.4 M), comparable with the commercial herbicide diuron (IC50 = 0.3 M).In chapter four the synthesis of 2,5-diaklylamino- and 2,5-diarylaminobenzoquinones is described through an established protocol using a 1:3 ratio of amine/quinone, affording 13 aminoquinones in favourable yields (46-93%). Reactions of these aminoquinones in their doubly-deprotonated form with dichloro p-cymene ruthenium (II) dimer, afforded 5 new dinuclear complexes in yields within 65-95%. All aminoquinones and their ruthenium complexes were evaluated against six different cancer cell lines. Results displayed values of effective concentration (EC50) higher than 60 µM for all the different cancer cell.Chapter five describes the synthesis of new derivatives to 8-hydroxy-2-methylquinoline in high yield (65-90%). These quinoline derivatives andcommercial 8-hydroxy-2-methylquinoline were reacted with dichloro p-cymene ruthenium (II) dimer, resulting 11 new ruthenium-quinolines complexes in 51-94% yields. For all quinolines derivatives and their complexes their antimicrobial activity against five microorganisms was evaluated. Results revealed active quinolines (5.6 and 5.4) with IC50 = 2.30 and 4.66 µg mL-1. Whereas for complexes (5.13 and 5.15) an increase in the antimicrobial activity was demonstrated, which presented IC50 as low as 9.37 and 4.64 µg mL-1.